Moon Knight. Vol. 4, Road to ruin - MacKay, Jed, 1983-; Lore, Danny (Marvel Worldwide, Inc., 2023)
Dreams and nightmares! Moon Knight wrestles with revelations from a savage murder - and there's more blood on the streets as assassins work their way through the list of names who once formed his Shadow Cabinet! But with a number of potential targets and no idea who's next, how can Moon Knight save his former associates? And when a sinister pied piper plays a deadly tune - one that spells death and chaos to all who hear it - Marc must figure out how to fight someone whose will is not their own!--